Cardiorespiratory fitness (CRF) and its relationship with maximum oxygen consumption (VO2max) among 16-year-old junior players at Zakho football club - Abdulsatar, Athraa Abdulelah (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. Cardiorespiratory fitness (CRF) plays a crucial role in modern football performance, particularly in youth development where proper assessment and monitoring can significantly impact long-term athletic potential. While laboratory-based measurements of maximum oxygen consumption (VO2 max) are accurate, there is a need to validate practical field-based testing methods for youth players, especially in regions with unique environmental conditions like Iraqi Kurdistan. The present study investigated the relationship between CRF and VO2 ma among 16-year-old football players at Zakho Football Club.Material and Methods. The descriptive correlational method was employed to examine the relationship between cardiorespiratory fitness CRF and VO2 max in 16-year-old junior football players. A random sample of twenty players was selected from a population of thirty-two players. The research utilized multiple assessment tools including the Cooper 12-minute test for CRF evaluation, heart rate monitoring through Garmin fÄ“nix ® 7 devices for measuring cardiovascular responses, and Cooper"™s formula for VO2 max estimation. Testing procedures were standardized and conducted at Dalal Sports Stadium during evening sessions to minimize environmental effects. Data analysis employed descriptive statistics and correlation coefficients.Results. The results revealed varying levels of cardiorespiratory fitness among players, with the majority demonstrating above-average performance levels. Statistical analysis showed a strong positive correlation between Cooper test performance and VO2 max values, validating the effectiveness of field-based testing for assessing cardiorespiratory fitness in Junior players. Heart rate response patterns indicated diverse cardiovascular adaptations across performance levels, suggesting the need for individualized training approaches.Conclusion. The findings contribute to understanding the relationship between field-based fitness assessments and physiological responses in Junior football, particularly in regions with unique environmental conditions. This research provides practical insights for optimizing Junior football development programs while highlighting the importance of considering individual adaptation patterns in training design.